ANALISIS BEBAN KERJA MENGGUNAKAN WORK LOAD ANALYSIS DENGAN PENDEKATAN SOFT SYSTEM METHODOLOGY DI PT INDORAMA PETROCHEMICALS - Ramadhania, Sherin; Rini, Asih Setyo; Herdiyani, Ahmad; Gunawan, Gunawan; Majdi, Nur Cholis (LPPM Universitas Bina Bangsa, 2024)
PT. Indorama Petrochemicals PT Indorama Petrochemical, producer of Purified Terephthalic Acid (PTA), has been operating since 2013. From production of 33 tons per hour, it has now reached 58 tons per hour. Indorama Chemical's PTA products are 100 percent absorbed for domestic needs including the textile industry as raw material for fiber and yarn. PT Indorama Petrochemical, producer of Purified Terephthalic Acid (PTA), has been operating since 2013. From a production of 33 tons per hour, it has now reached 58 tons/hour. Some examples of the problems that exist at the Chemical manufacturing company PT Indorama Cilegon include (lack of respect for employees, lack of man power, excessive workload, lack of safety/PPE awareness, lack of discipline and high work ethic). These problem factors result in low employee motivation at work, apart from that, employees will become less enthusiastic about achieving company targets and this will have an impact on a company and this can be detrimental to the company. The aim of this research is to reduce the physical workload experienced by employees at work by measuring workload using Work Load Analysis (WLA) with a Soft System Methodology (SSM) approach. In this research, an approach is needed to identify, measure and evaluate the amount of work or tasks that must be carried out in an organization or by a particular individual. System analysis is carried out to identify problems in a complex system and also to create solutions to improve existing problem solving. The results of this research are problem identification, causal loop diagram of excessive workload, rich picture of excessive workload, root definitions, conceptual model of increasing company productivity, and processes, as well as suggestions for improvement